SEKTOR INFORMAL DAN PENGUATAN KELEMBAGAAN LOKAL DALAM PENGELOLAAN SAMPAH TERPADU BERBASIS MASYARAKAT DI DESA KUTOHARJO KABUPATEN KENDAL - Rahdriawan, Mardwi (Jurnal Pengembangan Kota, 2013)
One of the environmental problems caused by human beings as a result of their activities is solid waste, the amount will be more and more, which can potentially lead to a variety of complex waste problems. Similarly, one of the central sub districts of the growing fast as urban areas, Desa Kutoharjo. The growing of heterogeneity of the population and land uses, it will emerge as problems of solid waste. Therefore, the village government through Community Self-reliance Agency (BKM) and non-governmental groups trying to implement the stages of sustainable waste management. Various attempts of implementation program has been done by community, such as sorting, âtakakuraâ or composting, but have not been able to run effectively. Along with it, the scavengers have been running their activities, who pick up trash sorting community property. So, the purpose of this article are to examines the activities and presence of scavengers in a state of society that seeks to manage the solid waste by strengthening local institutions in community-based integrated waste management. This article shows that the informal sector has been a well-established network, but it has become a community problem, if the scavengers take the solid waste sorting, especially on trash sorting, which is valuable if recycled. Most of the Scavengers has distinctive characteristics, namely do not care, ignorant with limited capabilities. Thus, their involvement in the management of Â community-based sustainable integrated waste is not easy and difficult to implement, especially most people have the same interests as scavengers. However, there are many scavengers-level collectors who can be trusted and people willing to work together with them, especially on trash sorting, such as plastic, metal, glass, paper, paperboard and etc. Therefore, its effectiveness for more sustainable waste management, formal and informal relations sector requires a better cooperation, due the informal sector already has a well established network to manage a solid waste and on the other side the local government officially through BKM that have been formed community groups of waste management.